Anatomical Fundamentals and Current Surgical Knowledge of Prostate Anatomy Related to Functional and Oncological Outcomes for Robotic-Assisted Radical Prostatectomy - Hoeh, Benedikt; Wenzel, Mike; Hohenhorst, Lukas; Köllermann, Jens; Graefen, Markus; Haese, Alexander; Tilki, Derya; Walz, Jochen; Kosiba, Marina; Becker, Andreas; Banek, Severine; Kluth, Luis A.; et al. (Frontiers in Surgery, 2022)
Context: Meticulous knowledge about the anatomy of the prostate and surrounding tissue represents a crucial and mandatory requirement during radical prostatectomy for reliable oncological and excellent replicable, functional outcomes. Since its introduction two decades ago, robotic-assisted laparoscopic radical prostatectomy (RALP) has evolved to become the predominant surgical approach in many industrialized countries. Objective: To provide and highlight current available literature regarding prostate anatomy and to help improving oncological and functional outcome in RALP. Methods/ Evidence acquiring: PubMed database was searched using the following keywords: ‘robotic-assisted radical prostatectomy’, ‘anatomy’, ‘neurovascular bundle’, ‘nerve’, ‘periprostatic fascia’, ‘pelvis’, ‘sphincter’, ‘urethra’, ‘urinary incontinence’ and ‘erectile dysfunction’. Relevant articles and book chapters were critically reviewed and if eligible, were included in this review. Results: New evidence in regards to prostatic anatomy and surgical approaches in RALP has been reported in recent years. Besides detailed anatomical studies investigating the meticulous structure of the fascial structures surrounding the prostate and neurovascular bundle preservation, debate about the optimal RALP approach is still ongoing, inspired by recent publications presenting promising functional outcomes following modifications in surgical approaches. Conclusions: This review provides a detailed overview of the current knowledge of prostate anatomy, its surrounding tissue and its influence on key surgical step development for robotic-assisted laparoscopic radical prostatectomy (RALP).